Synthesis of [1,5]-Benzodiazepino Derivatives - Nitu Gulia, Monika Chahar, Anil Narwal (Drugs and Cell Therapies in Hematology, 2021)
The heterocyclic compound [1,5]-benzodiazepino a has long history of public and scientific interest. If constitute an important class of psychopharmacopea, in particular as a tranquilizer and also as a non-nucleoside inhibitors of HIV-1 reverse transcriptase. Beside this, it is antibacterial, antidepressive, anticonvulsant, anti-inflammatory and sedative activities, some of its derivatives are used as dyes. Some allied derivatives of it are known to have muscle relaxant,antiobesity and. Benzimidazolinone condensed azepinone analogue from corresponding oxoketenedithioacetals and --unsaturead ketones have been described. Heterocyclic systems containing azepine and diazepine have attracted the attention of researchers due to their large number of applications in the human life. As a result of this there is no limit to the number of interesting ring systems that can be created in the laboratory today.